Recent Advancement of Fecal Microbiota Transplantation in the Treatment of Ulcerative Colitis- A Review - Lin, Yiting; Wang, Peiru; Hu, Xi; Wang, Qinjia; Shi, Quan; Zhou, Yanna; Liu, Ruisheng; Cai, Xianbin (Current Medicinal Chemistry, 2025)
Fecal Microbiota Transplantation (FMT) involves the transfer of gut microbiota from healthy donors to recipients, aiming to reestablish microbial equilibrium within the gastrointestinal tract. The human gut harbors a complex and diverse microbial ecosystem, comprising bacteria, viruses, and fungi, that is essential for maintaining intestinal homeostasis. Emerging evidence indicates a strong association between gut microbial dysbiosis and the pathogenesis of Ulcerative Colitis (UC). FMT has been shown to modulate microbial composition, alter immune signaling pathways, enhance intestinal barrier function, and influence the production of proinflammatory mediators, thereby affecting disease progression. This review critically examines the efficacy, safety, modulatory factors, combination therapies, and predictive strategies associated with FMT in the context of UC. The findings suggest that FMT represents a highly promising therapeutic modality for UC. Overall, this review aims to provide a comprehensive and impartial synthesis of current knowledge regarding FMT, offering deeper insights into its therapeutic potential and clinical applicability in UC management.
Keywords: gut microbiota